2022
DOI: 10.3390/jcm11020460
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Tourette Syndrome-Children’s and Parents’ Perspectives

Abstract: Tourette Syndrome (TS) is a neurodevelopmental condition characterized by the presence of tics and associated behavioral problems. Yale Global Tic Severity Scale (YGTSS), The PedsQL Pediatric Pain Questionnaire, and Pediatric Pain Coping Inventory were used to assess the severity of tics, the severity of the pain, the location of the pain and pain coping strategies both from children’s and parents’ perspectives. Sixty percent of children demonstrated pain (past or present); the pain was reported by 72% of pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Others have reported that approximately 60% of Tourette syndrome and tic disorder patients report pain with tics, and pain can be associated with significant tic-related disability. 30-32 Our findings provide additional, gender-specific information, with adolescent girls more likely to experience pain from their tics. Additional longitudinal studies are needed to probe specific impairments experienced by adolescents with painful tics.…”
Section: Discussionmentioning
confidence: 67%
“…Others have reported that approximately 60% of Tourette syndrome and tic disorder patients report pain with tics, and pain can be associated with significant tic-related disability. 30-32 Our findings provide additional, gender-specific information, with adolescent girls more likely to experience pain from their tics. Additional longitudinal studies are needed to probe specific impairments experienced by adolescents with painful tics.…”
Section: Discussionmentioning
confidence: 67%
“…Tic-related pain was shown to have a significant physical and psychological impact and was important to be addressed in the long-term management of tic disorders. A similar study was conducted in Poland ( Małek 2022 ) but this time in a pediatric population. The authors included 40 children with TS and 57 parents of children with TS, as they wanted to collect information about the perspective of children and parents on this topic.…”
Section: Resultsmentioning
confidence: 83%
“…Having long-standing tics is associated with a fourfold increased risk of death by suicide [ 18 ]. The impact of tics can be variable, affecting academic [ 19 ], social [ 20 22 ], occupational [ 19 ], and physical functioning due to pain [ 23 , 24 ]. Without adequate support, these factors can contribute to lower quality of life [ 1 ].…”
Section: Introductionmentioning
confidence: 99%